Physico-chemical, Thermal and Micro-structural Characterization of Four Common Banana Pseudo-Stem Fiber Cultivars in Nigeria. Issue 1 (31st December 2023) - Oyewo, Abideen Temitayo; Oluwole, Oluleke Olugbemiga; Ajide, Olusegun Olufemi; Omoniyi, Temidayo Emmanuel; Akhter, Parveen; Hamayun, Muhammad Haris; Kang, Bo Sung; Park, Young-Kwon; Hussain, Murid
ABSTRACT: This study explores Banana pseudo-stem fiber (BPSF) derived from BPF cultivars that are common in Nigeria. The four cultivars are known locally as Agbagba, Omini, Panbola, and Paranta. This study characterized these cultivars to gain insight into their physical, thermal and microstructural properties. The BPSFs were obtained after manual BPS retting and treated with a 2 wt. % sodium hydroxide solution to improve the fiber quality. Data from the characterization revealed the agbagba cultivar to give the highest percentage recovery (3%) and thermal stability at elevated temperatures with a residual char of 14%. The percentage of cellulose, lignin, hemicellulose, and ash content were determined by chemical composition analysis. FTIR spectroscopy showed a lower lignin and hemicellulose absorption band in the agbagba cultivar while scanning electron microscopy supported the FTIR results. Agabagba's crystallinity index (XRD) of 61.7% was higher than other cultivars, and X-ray fluorescence (XRF) and a biodegradation test also showed that only agbagba cultivar contained calcium and had the strongest resilience to microbial attack under simulated soil conditions. Agbagba BPSF may be a viable reinforcement in bio-fiber polymer composites needing high strength due to its balanced qualities that have been demonstrated in comparison to other cultivars.